Poslušati med vrsticami: parlamentarni govor in njegovi zapisi: Ina Poteko, Marko Stabej, Kaja Jošt - Krajnc Ivič, Mira (Stanje in perspektive uporabe govornih virov v raziskavah govora, 2024)
Listening Between the Lines: The Parliamentary Speech and Its Transcripts. As it is accessible and open source, parliamentary speech is valuable for research in various disciplines. Speeches delivered in parliament form the basis for the records contained in parliamentary corpora, but the recording practices of parliamentary services are usually not evident. In this paper, we present the practice of recording plenary sessions in the National Assembly of the Republic of Slovenia between 2010 and 2022 to document the process. In the Slovene Parliament, two versions are created: the first, quick transcript, which is published no later than half an hour after the speech to provide quick access to information, but which also contains some inaccuracies, and the second, verified transcript, which is created by listening to a recording of a speech and which is intended to be permanently published, accessible, and provides comprehensive information. We also present the recording practices of some other European parliaments for comparison.